Kebijakan Pendidikan Dan Pelatihan Bidang Teknis Di Badan Kepegawaian Dan Pengembangan Sumber Daya Manusia (BKPSDM) di Kabupaten Sanggau - Hiasinta Krisnawati; Herlan Herlan; Ira Patriani (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the implementation of technical education and training policies carried out by the Personnel and Human Resources Development Agency (BKPSDM) of Sanggau Regency. The main focus of the research is to evaluate the effectiveness of these policies in improving the quality of human resources among government apparatus, as well as to identify the supporting and hindering factors in their implementation. A descriptive qualitative approach was employed to gather data through interviews, observations, and document analysis. The findings indicate that although the technical education and training policies have been well formulated, their implementation still faces several challenges, such as limited supporting facilities, insufficient budget allocation, and inadequate capacity among training personnel. On the other hand, the policy has received support through the commitment of regional leaders and ongoing bureaucratic reform initiatives. These factors contribute to improving the performance of the apparatus, although the results have not yet reached optimal levels. This study recommends increasing the budget, providing additional training for instructors, and enhancing the availability of adequate facilities to support the successful implementation of technical education and training programs. Furthermore, periodic evaluations of policy implementation are expected to serve as a tool for identifying necessary improvements to achieve better governance in Sanggau Regency.